Between Kantian Rationalism and Moral Mysticism: The Search for the Grounding of Morality in the Philosophy of A. Jokubaitis - Noreikaitė, Aistė (Politologija, 2020)
Although it is common to associate the thought of A. Jokubaitis with political philosophy, this article argues that his texts also allow us to talk about a specific moral philosophy of A. Jokubaitis. At the center of it we find an attempt to articulate and discuss the grounding ideas of morality. The article argues that the first two ideas – an idea of unconditional character of morality and an idea of ontological grounding – are related to Kant’s influence on A. Jokubaitis philosophy. These two ideas allow us to explain morality as an autonomous part of reality, which is different from the empirical one but nonetheless real. This part of reality is grounded in the first-person perspective of a moral subject and can be characterized by implicit normativity and unconditionality. The first-person perspective structures a radically different relation to our reality, which allows us to be agents, not simply spectators. Such an interpretation of Kant allows to associate A. Jokubaitis with his contemporary Kantians, such as Ch. Korsgaard, B. Herman, O. O’Neill, and A. Reath. However, the third idea, the one of a person, which becomes more visible in his book Politinis idiotas, transcends the Kantian conception of practical reason and encourages to perceive morality and its grounding in a much wider context. The concept of a person allows A. Jokubaitis to distance himself from Kantian rationalism and integrate social and mystical aspects of morality, which he has always found important.
Keywords: Jokubaitis; Kant; Kantian ethics; moral philosophy; political philosophy; grounding of morality; first-person perspective